Decontextualized talk in caregivers' input to 12-month-old children during structured interaction. Issue 2 (21st March 2020) - GRIMMINGER, Angela; ROHLFING, Katharina J.; LÜKE, Carina; LISZKOWSKI, Ulf; RITTERFELD, Ute
Abstract: Decontextualized talk is assumed to be used only rarely when children are younger than 30 months. Motivated by Bühler's (1934/1999 ) linguistic theory that describes different dimensions of (de-)contextualization, we provide evidence that this kind of input can already be found in caregivers' talking to their 12-month-old children. Such early input is characterized by being decontextualized on some dimensions while being grounded in the immediate context on others. In this way, parents may scaffold understanding of talk about the there-and-then . We also examined whether caregivers adapt decontextualized verbal input to individual trajectories in language development. We observed 59 parent–child interactions within a decorated room when children were 12 months old, and assessed the children's linguistic development at 12 and 24 months of age. However, we did not find differences in the input directed toward children with different trajectories in language development.